2023
DOI: 10.3389/fnut.2023.1160069
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the mechanism of jujube vinegar on hyperlipoidemia through gut microbiome based on 16S rRNA, BugBase analysis, and the stamp analysis of KEEG

Abstract: BackgroundGrowing data indicate that the gut microbiome may contribute to the rising incidence of hyperlipoidemia. Jujube vinegar lowers lipids, protects the liver, and reduces oxidant capacity, however, it is unknown whether this is due to the gut flora. To further research the role of the gut microbiome in treating hyperlipidemia with jujube vinegar, we looked into whether the action of jujube vinegar is related to the regulation of the gut microbiome.MethodThirty male ICR mice were used. The control group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…To further confirm the effects of L-27-2, L-14-1, and F203 on blood lipids, the blood lipid content (TG, TC, LDL-C, and HDL-C) of mice was biochemically analyzed. The results showed that the increase in TC, TG, and LDL-C was closely related to hyperlipidemia, obesity, and other diseases ( Retterstøl et al, 2018 ; Webb et al, 2022 ; Duan and Li, 2023 ). However, all three strains can reduce TG in serum, however, TC and LDL-C showed only a decreasing tendency, and their differences with M group were not significant ( P > 0.05) ( Figures 6A, C ).…”
Section: Resultsmentioning
confidence: 97%
“…To further confirm the effects of L-27-2, L-14-1, and F203 on blood lipids, the blood lipid content (TG, TC, LDL-C, and HDL-C) of mice was biochemically analyzed. The results showed that the increase in TC, TG, and LDL-C was closely related to hyperlipidemia, obesity, and other diseases ( Retterstøl et al, 2018 ; Webb et al, 2022 ; Duan and Li, 2023 ). However, all three strains can reduce TG in serum, however, TC and LDL-C showed only a decreasing tendency, and their differences with M group were not significant ( P > 0.05) ( Figures 6A, C ).…”
Section: Resultsmentioning
confidence: 97%
“…To ascertain whether bacterial genera were significantly enriched, linear discriminant analysis (LDA) effect sizes (LEfSe) (Segata et al, 2011) were employed (LDA scores >3, p < 0.05). To anticipate the phenotypic function of each plaque sample group, overexpression phenotypes were identified using BugBase (Duan and Li, 2023). Statistical analyses were performed using SPSS 25.0 (IBM Corporation, Armonk, NY, United States).…”
Section: Discussionmentioning
confidence: 99%